Natural Products for Chronic Diseases: A Ray of Hope - Hassan, Syed Shams ul; Abdel-Daim, Mohamed M.; Behl, Tapan; Bungau, Simona Gabriela (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Pharmacology and Pharmacognosy is organized into twelve articles that explore therapeutic potential of different natural products from land and marine. The articles contain highly detailed coverage of information that has been overseen by an editorial board made up of well-respected, field-leading experts. The content in this book offers readers an in-depth and easily accessible reference work on every aspect of natural product research surrounding the pharmacology, medicinal chemistry, pharmacognosy, and bioinformatics of all natural products and their scaffolds, their mechanism of action, and their therapeutic values. These elements are essential to be selected as future drugs are almost never tested and developed in the actual therapeutic system, but rather in test systems from which parameters must be determined to predict activity in systems of varying ambient physiology. As different technologies rapidly evolve, there is an ever-increasing level of knowledge about the natural products, along with increasing capability to utilize bioactive molecules to predict new drugs against chronic diseases, all of which must be communicated to professionals in varying fields.